Affective touch reduces histamine evoked itch experience - Syed Hasan Ali; Nicholas Fallon; Timo Giesbrecht; Andrej Stancak; Carl A Roberts (PLoS ONE, 2025)
Itch is a commonly experienced symptom of skin diseases such as eczema. Topical corticosteroid medications are widely used in chronic itch conditions but can lead to skin thinning, and in certain cases, topical corticosteroid withdrawal. As such, non-pharmaceutical alternatives are being researched. The present research explored affective touch (slow stroking, gentle touch signalled by C-tactile afferents) as a strategy to reduce histamine induced itch. Whilst experiencing histamine induced itch on the volar side of the forearms/wrist, participants (n = 60) were subjected to 3 experimental conditions of modulatory somatosensation applied to the volar aspect of the same forearm relative to the site of itch induction (18 trials of each); 1) affective touch (stroking the forearm with a soft brush at 3 cm/s), 2) non-affective touch (stroking the forearm with a soft brush at 18 cm/s) and 3) active control (static brush tapping on the forearm at 1Hz). Participants were asked to rate the severity of itch, and pleasantness of touch, after each trial. We also investigated whether changes in itch severity scores during the affective touch condition were moderated by individual differences in somatosensory experiences and attitudes as measured on the Touch Experiences and Attitudes Questionnaire (TEAQ), and the Pain Vigilance and Awareness Questionnaire (PVAQ). A linear mixed effects model indicated a main effect of condition on itch severity, whereby affective touch significantly reduced itch severity compared to non-affective touch (p < .001) and active control (p < .001). The TEAQ and PVAQ scores did not correlate significantly with itch scores in the affective touch condition. These results suggest that affective touch has a relieving effect on histamine-induced itch. Our findings lend further credibility to the idea that affective touch might be able to serve as an effective non-pharmaceutical treatment of itch conditions complementing established approaches.